Rancang Bangun Sistem Informasi Customer Relationship Management Terhadap Penilaian Pelanggan Berbasis Web - Andri Cahyo Purnomo; Nur Felia; Halimah Febbi Budiana (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2021)
The problem that occurs is that the CRM (Customer Relationship Management) system is still semi-computerized, namely using Microsoft Excel for data processing. Resulting in problems, among others: slow customer service, and the company's response to customers is not optimal. To overcome this, a website-based application is needed to solve the problems that are happening today. In designing the application, it uses SWOT analysis and UML (Unified Modeling Language) diagrams, and uses the PHP (Hypertext Preprocessor) programming language, Codeigniter Framework, XAMPP. The database server uses MySql and Sublime Text 2 as a text editor. So that with this application customer assessment becomes efficient and optimal.